DNA-PK inhibition by M3814 enhances chemosensitivity in non-small cell lung cancer - Manni Wang; Siyuan Chen; Yuquan Wei; Xiawei Wei (Elsevier, 2021)
A significant proportion of non-small cell lung cancer (NSCLC) patients experience accumulating chemotherapy-related adverse events, motivating the design of chemosensitizating strategies. The main cytotoxic damage induced by chemotherapeutic agents is DNA double-strand breaks (DSB). It is thus conceivable that DNA-dependent protein kinase (DNA-PK) inhibitors which attenuate DNA repair would enhance the anti-tumor effect of chemotherapy. The present study aims to systematically evaluate the efficacy and safety of a novel DNA-PK inhibitor M3814 in synergy with chemotherapies on NSCLC. We identified increased expression of DNA-PK in human NSCLC tissues which was associated with poor prognosis. M3814 potentiated the anti-tumor effect of paclitaxel and etoposide in A549, H460 and H1703 NSCLC cell lines. In the four combinations based on two NSCLC xenograft models and two chemotherapy, we also observed tumor regression at tolerated doses in vivo. Moreover, we identified a P53-dependent accelerated senescence response by M3814 following treatment with paclitaxel/etoposide. The present study provides a theoretical basis for the use of M3814 in combination with paclitaxel and etoposide in clinical practice, with hope to aid the optimization of NSCLC treatment.